SUD und Solidaires: Linksalternative Basisgewerkschaften in Frankreich - Schmid, Bernard (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
Left grass-root oriented unionism in France, In the late 80ies some new trade unions were founded in France, trying not to loose contact to the members and arguing for a new social project of change against neoliberalism, Originally rooted in public services, in the 90ies SUD spread to further branches, Until now it is a small but quickly growing organisation, important in all social conflicts in France during the last years,